The treatment of acute bronchiolitis: past, present and future - Petrarca, Laura (2019)
Lower respiratory tract infections are a common cause of hospitalisation in infants. It is estimated that infants younger than 12 months with bronchiolitis account for 18% of all paediatric admission [1], representing a great burden to industrialised healthcare systems each winter. Bronchiolitis is defined as the first respiratory tract infection in infants younger than 12 months. Clinically, it can be manifested by cough, tachypnoea, apnoea, increased respiratory effort, fever, nasal congestion and rhinorrhoea. On chest auscultation, the key feature is diffuse bilateral inspiratory crackles. The most common virus detected in children with bronchiolitis is respiratory syncytial virus (RSV)